The Influence of Product Quality, Reputation, and Trust on Purchasing Decisions at PT Semarak Konstruksi Batam - Lestari, Elisa Jayanti (Universitas Mercu Buana, 2024)
Digital marketing has revolutionized business-consumer interactions by providing unprecedented global reach and opportunities for influence. One notable example of this digital marketing transformation is the experience of